Delayed recognition of autism spectrum disorder and attention-deficit/hyperactivity disorder in a girl with ornithine transcarbamylase deficiency: A case report. Issue 8 (22nd February 2023) - Kadono, Shin; Miyawaki, Dai; Goto, Ayako; Hirai, Kaoru; Sakamoto, Shoko; Hama, Hiroki; Nishiura, Sayaka; Hamazaki, Takashi; Inoue, Koki
Abstract : Rationale: Ornithine transcarbamylase (OTC) deficiency, a urea cycle disorder, is a rare congenital metabolic error that leads to hyperammonemia. Psychiatric symptoms of hyperammonemia are nonspecific and can cause autism spectrum disorder (ASD)-like symptoms and attention-deficit/hyperactivity disorder (ADHD)-like symptoms. Some studies report that OTC deficiency is often initially diagnosed as ASD or ADHD. However, there are no reports of OTC deficiency comorbid with ASD and ADHD. Patient concerns: The patient is 17-year-old girl diagnosed with OTC deficiency at 3 years of age. She had behavioral problems since childhood, including depressed mood, irritability, and impulsive behavior; however, they were considered OTC-mediated nonspecific psychiatric symptoms. Therefore, the patient had not been appropriately assessed for ASD and ADHD. She presented with depressed mood and self-harm at 17 years of age. Diagnoses: We diagnosed her with ASD and ADHD based on her medical history and semistructured interviews. Interventions: We focused her ASD and ADHD traits and discussed strategies with her for better adaptive living. Outcomes: Our interventions resulted in her better social adjustment. Lessons: Physicians should consider the possibility of comorbid ASD and ADHD in individuals with OTC, facilitating appropriate and intervention for better outcomes.